1977
DOI: 10.1007/bf00498557
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sr2+ and Mg2+ on the phospholipase A and the presynaptic neuromuscular blocking actions of ?-bungarotoxin, crotoxin and taipoxin

Abstract: 1.beta-Bungarotoxin, crotoxin and taipoxin, presynaptic neurotoxins of snake venom origin, have about the same phospholipid-splitting activities as a much less toxic cobra phospholipase A2 in the presence of Ca2+ and deoxycholate. 2. Sr2+ was a much less effective activator of the enzymes than is Ca2+, the activation by Sr2+ being only 3-6% for beta-bungarotoxin and crotoxin and 12% for taipoxin. 3. Sr2+ also inhibited the Ca2+ -activated enzymes by 80% in the cases of beta-bungarotoxin and crotoxin, but only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1

Year Published

1978
1978
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(22 citation statements)
references
References 25 publications
0
21
1
Order By: Relevance
“…This is likely due to the fact that the Mt-I alteration of the sarcolemma is mediated by PLA 2 phospholipid hydrolysis, which in turn requires some time to produce enough lysophospholipids and fatty acids to increase sarcolemmal permeability. Snake PLA 2 toxins are highly dependent on Ca 2+ for their enzymatic activity and are inhibited by Sr 2+ (34,35). Indeed, the substitution of Sr 2+ for Ca 2+ in the medium largely prevented K + release (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…This is likely due to the fact that the Mt-I alteration of the sarcolemma is mediated by PLA 2 phospholipid hydrolysis, which in turn requires some time to produce enough lysophospholipids and fatty acids to increase sarcolemmal permeability. Snake PLA 2 toxins are highly dependent on Ca 2+ for their enzymatic activity and are inhibited by Sr 2+ (34,35). Indeed, the substitution of Sr 2+ for Ca 2+ in the medium largely prevented K + release (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…They used 20-fold more toxin than we used, and at this concentration the amount of PLA activity may obscure the inhibition because events responsible for the rebound may begin much earlier. The results of Chang and Lee (24) and Chang et al (25) suggest that this may be true, because they can only see the initial inhibition of twitch tension when PLA activity is greatly reduced. Strong et al (12) made their measurements at least 10 min after the addition of the toxin, and this may be at a time after the initial inhibition has occurred and the rebound begun, especially with higher concentrations of toxin.…”
Section: Resultsmentioning
confidence: 99%
“…They have reported an initial inhibition of twitch tension, a subsequent rebound in tension, and a gradual decay of twitch tension resulting in complete blockade of transmission when their rat diaphragm preparation was exposed to the 22,000-dalton toxin in lowcalcium (0.18 mM) saline. In addition, Chang et al (25) recently demonstrated that the initial blockade was also seen when the PLA activity of the toxin was partially inhibited by replacing calcium with strontium in the bathing solution, and suggested that this inhibition of the toxin was due to an action other than the PLA activity. Thus, the 11,000-and 22,000-dalton (3-BuTXs appear to have similar modes of action.…”
Section: Resultsmentioning
confidence: 99%
“…In the first, preparations were pretreated with one of the facilitatory toxins and then the time taken for one of the blocking toxins to inhibit responses to indirect stimulation was measured. In the second, preparations were exposed to one of the blocking toxins before the addition of a facilitatory mamba toxin; these experiments were performed in physiological salt solution in which Ca2+ was replaced by 2.5 mM Sr2' as Sr2+ inhibits the phospholipase A2-dependent blocking activity, but not the binding, of the prejunctional blocking toxins (Chang, Su, Lee & Eaker, 1977;Caratsch, Maranda, Miledi & Strong, 1981;Harris & MacDonell, 1981). To show that any interaction was not simply a consequence of the increased transmitter release caused by the mamba toxins, parallel experiments were performed with 3,4-diaminopyridine.…”
Section: Interactions Of the Facilitatory Neurotoxins With Prejunctiomentioning
confidence: 99%